NEW PARADIGM OF DRUG COMBINATION FORMULATION FOR PSOARIASIS THERAPY AND ITS SUPERIORITY COMPARED BY STANDARD THERAPY - Sukmawati Tansil Tan; Yohanes Firmansyah (Jurnal Medika Hutama, 2021)
Background: Psoriasis is a chronic inflammatory skin disease characterized by persistent itching and a high rate of recurrence. Until now, the primary issue with these two diseases has been their inability to respond to therapy; thus, it is critical to develop an appropriate combination therapy for these two diseases. Due to the fact that psoriasis patients experience alternating periods of remission and exacerbation, dermatologists should tailor psoriasis treatment to the severity of the disease at the time it manifests, with the goal of extending remission and improving quality of life. Thus, it is critical to achieve maximum treatment efficiency in order to prolong the period of remission and improve quality of life. Method: This study is a study comparing the effectiveness of a new treatment therapy using a combination therapy of 0.05% Clobetasol with 3% liquor carbonis detergent and 2% salicylic acid compared to standard therapy, namely 0.05% Clobetasol. This study is a restrospective cohort therapy at the Indra Clinic. The samples of this study were all cases of psoariasis of the skin at Indra's clinic in the 2016-2017 period that met the inclusion criteria. The independent variable of this study was the drug formulation with the dependent variable in the form of clinical improvement and the appearance of side effects. Results: The cure rate was 86,2 percent for the 29 respondents who received the combination formulation, compared to 54,5 percent for the 22 respondents who received standard therapy containing Clobetasol 0.05 percent (p : 0,028). There were no statistically significant differences in adverse events between the two intervention groups. Conclusion: Innovative drug formulations (clobetasol 0.05% with 3% liquor carbonis detergent and 2% salicylic acid) for psoariasis are proven to be more effective and superior than standard therapies